Pengaruh Penerapan E-Filing, Tapping Box dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak (Studi Kasus di Kota Pekanbaru) - M Arief; Dwi Fionasari; Adriyanti Agustina Putri; Wira Ramashar (Politeknik Negeri Bengkalis, 2021)
ABSTRACTÂ This study aims to examine whether there is an effect between the application of e-filing, tapping boxes and tax sanctions on taxpayer compliance. The data used in this study are primary data. This type of research is quantitative. The object of this research is a restaurant that has an NPWP and has a transaction recording device (tapping box) in Pekanbaru City. The method of collecting samples using purposive sampling method. The population of this research is the taxpayer of restaurant entrepreneurs in Pekanbaru City. Samples were taken as many as 150 restaurants. The data analysis test uses multiple linear regression method which is processed using SPSS 21. The results of this study indicate that the variables of the use of e-filing, tapping boxes and tax sanctions have a positive effect on taxpayer compliance.Â Keywords: Use of E-Filing, Tapping Box, Tax Sanctions and Taxpayer ComplianceÂ